Association of Serum Vitamin D With Psoriasis and Effect Modification by Central Obesity - Kuang, Yehong; Xiao, Yi; Fang, Zhiqin; Zhang, Yichi; Shen, Minxue; Chen, Xiang; Chen, Mingliang; Lv, Chengzhi; Zhu, Wu (Frontiers in Medicine, 2020)
Background: Psoriasis is a chronic recurrent inflammatory disease involving many common mechanisms associated with obesity, such as systemic inflammation and vitamin D deficiency. This study aimed to examine the association of the serum concentration of 25-hydroxyvitamin D with psoriasis and the effect modification by obesity among the affected patients. Methods: A mixed cross-section study was conducted. We consecutively included untreated psoriasis patients from the outpatients who visited the Department of Dermatology of Xiangya Hospital and recruited 205 gender-matched healthy controls from the Hunan Civil Servant Cohort. In both groups, we measured the serum 25-hydroxyvitamin D level, body mass index (BMI), waist-hip-ratio (WHR) and other psoriasis-related clinical indicators. Results: A total of 203 psoriasis outpatients and 205 gender-matched cohort participants with complete data of serum vitamin D concentration were included in the analysis. The serum vitamin D levels of the two groups were close to each other, while the mean WHR of the psoriasis outpatients was significantly higher. Compared with the controls, the risk of psoriasis increased significantly when the vitamin D level decreased from 20 to 10 nmol/L. A significant interaction between the serum vitamin D level and the obesity category (BMI × WHR) was identified. After stratification by WHR, vitamin D was not associated with psoriasis in subjects with normal WHR. In contrast, the association between vitamin D deficiency and psoriasis retained and the effect size augmented in patients with central obesity. Conclusions: WHR may modify the association between serum vitamin D and psoriasis. Treatment advocating Vitamin D supplements may tailor to psoriasis patients with metabolic disorders.